Development of Biodegradable Polycation-Based Inhalable Dry Gene Powders by Spray Freeze Drying - Tomoyuki Okuda; Yumiko Suzuki; Yuko Kobayashi; Takehiko Ishii; Satoshi Uchida; Keiji Itaka; Kazunori Kataoka; Hirokazu Okamoto (MDPI AG, 2015)
In this study, two types of biodegradable polycation (PAsp(DET) homopolymer and PEG-PAsp(DET) copolymer) were applied as vectors for inhalable dry gene powders prepared by spray freeze drying (SFD). The prepared dry gene powders had spherical and porous structures with a 5~10-μm diameter, and the integrity of plasmid DNA could be maintained during powder production. Furthermore, it was clarified that PEG-PAsp(DET)-based dry gene powder could more sufficiently maintain both the physicochemical properties and in vitro gene transfection efficiencies of polyplexes reconstituted after powder production than PAsp(DET)-based dry gene powder. From an in vitro inhalation study using an Andersen cascade impactor, it was demonstrated that the addition of l-leucine could markedly improve the inhalation performance of dry powders prepared by SFD. Following pulmonary delivery to mice, both PAsp(DET)- and PEG-PAsp(DET)-based dry gene powders could achieve higher gene transfection efficiencies in the lungs compared with a chitosan-based dry gene powder previously reported by us.